Síntese de carbono mesoporoso derivado de amido e laponita como molde inorgânico para adsorção de surfactante - Gonçalves, Rosembergue Gabriel Lima (2016)
This work aims at describing the preparation of a type of mesoporous carbon (MC) based on biomass using a lamellar silicate mold and a pyrolytic synthesis technique. The MC was prepared by the addition of an aqueous colloidal dispersion of particles of synthetic clay Laponite RD in a dispersion containing gelatinized cassava starch (AM) in a ratio of 50/50 polymer/clay (% m/m). The gel produced from the mixture of clay and AM was dried, originating an organic-inorganic hybrid compound (HA50%), which was pyrolyzed under nitrogen flow at 850 °C. The inorganic material produced from the thermal decomposition was removed by washing with HF and HCl solutions, yielding the MC. This resulting material was used in simulated tests for the decontamination of effluents contaminated with surfactants. The material produced was characterized by a series of tests: powder X-ray diffraction (XRD), measurement of BET specific surface area, and scanning electron microscopy (SEM). The MC was used as an adsorbent for removing the surfactants Sodium dodecylbenzenesulphonate (SDBS) and cetyltrimethylammonium bromide (CTAB) in aqueous solution. The evaluation of the surface area analysis and medium size pores demonstrated that MC had a high surface area (1008 m2·g-1) with typical isotherm of mesoporous materials and average pore size was found to be approximately 50 Å. The adsorption of surfactants followed the typical behavior of the Langmuir isotherm model and the kinetic model was considered as pseudo second order. The maximum adsorption capacity of surfactants in the MC was 724.57 mg· g-1 for SDBS and 658.15 mg· g-1 for o CTAB.